Effects of salinity and driving pressure on water imbibition during shale formation - Xianyu Shao; Wang, Ke; Lingyun Zhao; Chao Su; Daquan Zhang; Wei Gao (Capillarity, 2024)
During the construction stage of underground engineering projects, the engineering fluids used often carry a certain level of pressure, and rock formations in the subsurface invariably contain fluids with a certain degree of salinity. Both the driving pressure in engineering fluids and the high degree of salinity in the original subsurface fluids will inevitably impact the entire imbibition process; however, despite the high relevance to actual engineering situations, these effects have not been systematically studied in traditional researches on imbibition. In this study, imbibition experiments under varying engineering conditions, such as water salinity, driving pressure and initial water saturation, are conducted to detect the actual imbibition phenomenon in underground engineering projects. In addition, a modified Handy model considering the above three factors is proposed to better predict the imbibition law of shale under actual engineering conditions. The results show that salinity and driving pressure have significant effects on water imbibition, while the modified model, possessing exceptionally high fitting accuracy, effectively characterizes the forced imbibition patterns of shale. This study provides new insights into investigating fluid imbibition phenomena in the development stage of underground engineering. Document Type: Original article Cited as: Shao, X., Wang, K., Zhao, L., Su, C., Zhang, D., Gao, W. Effects of salinity and driving pressure on water imbibition during shale formation. Capillarity, 2024, 11(3): 70-80. https://doi.org/10.46690/capi.2024.06.02